'Peaceful civil jihad' – Saudi Arabia's Islamic civil rights movement and its concept of jihad. Issue 1 (2nd January 2022) - Enz-Harlass, Peter
Abstract: In the 2000s CE, Saudi Arabia saw the emergence of the civil rights group HASM (or ACPRA), whose members engaged in civil society activism for basic rights and argued that their activism could be described as peaceful, civil jihad. In their books, declarations and lectures, HASM's members presented a complex Islamic theory of civil society activism and explained why they considered what they were doing legitimate. Their theory above all rested on the idea that civil society activism was a form of jihad and superior of other forms, like military jihad. This paper focusses on HASM's concept of peaceful, civil jihad. It is a complex concept, which is based on the ideas of some twentieth and twenty-first century Islamic scholars, but nevertheless constitutes a new interpretation of the term jihad. HASM's idea that civil society activism is peaceful, civil jihad is not only relevant in the Saudi context. Rather, it is a significant contribution to the ongoing debate about the meaning of jihad in modern Muslim societies.